Strategic Policy Overreaction as a Risky Policy Investment - Moshe Maor (International Review of Public Policy)
Policy overreaction is a policy that imposes objective and/or perceived social costs without producing offsetting objective and/or perceived benefits. It is therefore an objective fact and, at the same time, a matter of interpretation. Policy scholars tend to view this duality as a problematic ontological issue and to categorize such policies as errors of commission or omission. This article builds on (i)the aforementioned duality and (ii)a recent conceptual turn whereby this concept is re-entering the policy lexicon as a type of deliberate policy choice. This may be motivated by, among other factors, political executives’ desire to pander to public opinion, appear informed to voters, and signal extremity. The article assigns specific policy overreaction responses to two dimensions: the scale of policy in terms of objective costs and benefits, and public perceptions of policy. The derived policy taxonomy highlights four distinct empirical categories, which are elaborated and exemplified here, as well as a set of hypotheses about differing patterns of politics and governance associated with the design of these policy choices. These distinctions should facilitate a more systematic empirical test of strategic policy overreaction as a risky policy investment.